A dictionary of social work and social care - Harris, John; White, Vicky (Oxford, United Kingdom : Oxford University Press, 2018)
This dictionary provides A-Z definitions of terms from the broad field of social care. Accessible coverage of social work theories, methods, policies, organisations, and statutes, as well as key terms from interdisciplinary topics such as health and education, make this an ideal reference for students as well as qualified social workers.
Preface List of contributors Dictionary of Social Work and Social Care A-Z Table of Legislation, Regulations, and Codes of Practice Acronyms.
Includes bibliographical references .
Keywords: Dictionary; Medical care Dictionaries; Social service Dictionaries